2005
DOI: 10.2139/ssrn.754805
|View full text |Cite
|
Sign up to set email alerts
|

Children's Consumption of WIC-Approved Foods

Abstract: The WIC program offers supplemental foods to low-income women, infants, and children. This study compared consumption patterns of WIC children with those of three different comparison groups: eligible nonparticipating children living in non-WIC households, eligible nonparticipating children living in WIC households, and children living in households whose income is too high to be eligible for WIC. The study provides strong evidence that participation in the WIC program increases consumption of at least some ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 6 publications
0
16
1
Order By: Relevance
“…There were no detectable differences in sugar intake between children on WIC and their non-WIC, income-eligible counterparts. An earlier study [8] found that children in WIC households, whether direct participants or not, consumed more of certain WIC foods than children in non-WIC households (whether income-eligible or not). This study found increased calorie intake from WIC foods, but not significant differences in calorie intake overall.…”
Section: Introductionmentioning
confidence: 94%
“…There were no detectable differences in sugar intake between children on WIC and their non-WIC, income-eligible counterparts. An earlier study [8] found that children in WIC households, whether direct participants or not, consumed more of certain WIC foods than children in non-WIC households (whether income-eligible or not). This study found increased calorie intake from WIC foods, but not significant differences in calorie intake overall.…”
Section: Introductionmentioning
confidence: 94%
“…Table 2.3 contains the description of WIC-approved milk and cheese selected for the analysis. We followed closely the selection of WIC-approved foods done by Oliveira and Chandran (2005). Consumption of milk and cheese is analyzed regardless of whether the food was actually purchased through WIC.…”
Section: Empirical Analysis Model and Estimationmentioning
confidence: 99%
“…There is a well established literature on the effect of WIC participation on health and nutrient intake of infants, toddlers and children Oliveira and Gundersen, 2000;Ponza, et al 2004;Rose, et al 1998;Siega-Riz, et al 2004;Oliveira and Chandran, 2005). Considerable work has also been done to evaluate the effect of the WIC participation on pregnant women (Kowaleski-Jones andDuncan, 2002, Bitler andCurrie, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations